System dynamics modeling on new generation cooperative as an alternative to enhance bargaining position of potato farmers in Bener Meriah district. Issue 1 (November 2021) - Baihaqi, A; Hakim, L; Marsudi, E; Zulkarnain
Abstract: This study aims to create a New Generation Cooperative (NGC) model in potato supply chain in Bener Meriah District, which is also the subject of research, by applying the system dynamics method to build a dynamic and complex NGC model. This modeling is carried out as an effort to enhance bargaining position at farm level. The result showed that non-formal partnership relationship in potato supply chain is originated from the gap in capital ownership between farmers and intermediary traders, thus giving rise to motivation to control farmers by providing financial loan to farmers. Loan recipient farmers must commit to sell potato only to financial aid traders. This causes the loss of opportunity to sell potato to other parties, which has an impact on the occurrence of pressure on selling price of farmers's potato. Farmers face asymmetry information, especially regarding the selling price prevailing in the market. On the other hand, formal partnership starts with the industry motivation that is to obtain raw materials, that meet quality requirements on an ongoing basis. In a formal partnership, technology transfer occurs from partners to farmers. Farmers get marketing and price certainty, wider marketing access, and have the opportunity to earn higher profits. Based on the simulation results, data obtained that farmers who are the NGC members get higher revenue, profit, and business efficiency level, than non-partnership farmers.